PEMBELAJARAN PROBLEM-BASED LEARNING DALAM MENUMBUHKAN MORAL DAN EMPATI PESERTA DIDIK - Husnul Khatimah Arifuddin; Tenri Ninin Nur; Hilyatul Azizah; Julianus Paseno; Burhan; Muh. Yunus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to philosophically analyze Problem-Based Learning in fostering students’ morality and empathy in elementary schools. The study employed a qualitative approach using a library research design. Data were collected through documentation techniques from various relevant primary and secondary literature sources, including the thoughts of educational philosophers, academic books, and previous studies related to Problem-Based Learning, morality, and empathy. Data analysis was conducted using content analysis combined with philosophical interpretation through the stages of data reduction, data presentation, and systematic conclusion drawing.The findings indicate that ontologically, Problem-Based Learning views students as active subjects who construct their knowledge through direct experiences and social interaction. Epistemologically, knowledge in Problem-Based Learning is constructed through contextual, critical, and reflective problem-solving processes. Furthermore, axiologically, Problem-Based Learning possesses values that contribute to students’ character formation, particularly in developing morality through value-based decision-making and fostering empathy through collaboration and group discussions.Therefore, Problem-Based Learning has a strong philosophical foundation in supporting humanistic, contextual, and meaningful learning for elementary school students.